Pelatihan Editing Video dan Youtube Creator Menggunakan Aplikasi Filmora Guna Meningkatkan Kreativitas Bidang Pemasaran Online di Desa Bumi Agung Pesawaran - Robi Santoso; Denny Kurniawan; Ilham Setio Wibowo; Harits Kurniawan (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2024)
Community Service is a process of devotion through various direct activities in the midst of the community, lecturers and students strive to be part of the community and actively and creatively involved in the dynamics that occur in the community. Lecturers and students have a strategic role as agents of change. Based on the results of the observation, the work program for Video Editing training using the Filmora application was determined to be carried out using the lecture method followed by direct practicum by making examples of intro videos with the Filmora application. One of the formats that is currently a favorite of trademark owners and their own services is endorsement via content creators. This is considered more effective because it can reach more business people with similar interests with the target audience that suits what they want.